Skills Required to Head Physician for the Management of Staff. Emotions in the Organizational Context - Mango Lucio; Di Stefano Giuseppe (Journal of Public Health International, 2018)
This short paper aims to identify the key skills required for personnel management that makes it possible a peaceful business climate and a level of excellence in services rendered. Are analyzed particularly emotional skills like e.g. mindfulnessa
Keywords: personnel Management